STUDIES ON THE EFFECT OF NERIUM FLOWERS PRESENCE IN REARING BED ON HAEMOLYMPH TREHALOSE DURING FIFTH INSTAR OF MULTIVOLTINE SILKWORM, BOMBYX MORI - SUJATHA, K.; RAO, A. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The phytochemical effect of nerium flowers on haemolymph trehalose of fifth instar larvae of pure Mysore race was studied by continuously exposing silkworms from 1" day of instar I and upto harvest of cocoons to fully bloomed flowers of nerium introduced in the rearing bed. However, after III moult the worms were separated into batches and reared separately on leaf and shootlets in trays. In the shoot rearing minimum increase of the trehalose 19.5% was found on 5" day while maximum content of 34.8% was found on 1" day. However, with leaf rearing method, the lowest of 26.2% was found on the 5" day and highest increase of trehalose content (33.23%) was found on the 3" day.